2019
DOI: 10.1353/pbm.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

The New Science of Practical Wisdom

Abstract: sophical texts. It is often viewed as a fuzzy psychological construct analogous to consciousness, stress, and resilience. This essay provides an understanding of wisdom as a scientific construct, based on empirical research starting in the 1970s. The focus is on practical rather than theoretical wisdom. While there are different conceptualizations of wisdom, it is best defined as a complex human characteristic or trait with specific components: social decision-making, emotional regulation, prosocial behavior (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 50 publications
1
21
0
4
Order By: Relevance
“…It has several components: pro-social behaviors including empathy, compassion, altruism, and a sense of fairness; decision-making, emotion regulation, self-reflection or insight, acceptance of uncertainty or divergent perspectives, decisiveness or ability to make timely or effective decisions, general knowledge of life and social decision making and spirituality. 14 , 15 Wisdom is associated with well-being, happiness, life satisfaction, and resilience. Possessing and nurturing wisdom is extremely important for individuals and society.…”
Section: Introductionmentioning
confidence: 99%
“…It has several components: pro-social behaviors including empathy, compassion, altruism, and a sense of fairness; decision-making, emotion regulation, self-reflection or insight, acceptance of uncertainty or divergent perspectives, decisiveness or ability to make timely or effective decisions, general knowledge of life and social decision making and spirituality. 14 , 15 Wisdom is associated with well-being, happiness, life satisfaction, and resilience. Possessing and nurturing wisdom is extremely important for individuals and society.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, extended family households may include extra caregivers who also provide extra income which may be beneficial to children’s behavior development [ 18 ]. Further, studies have found that children who grow up with their grandparents live longer and are happier, and that grandparents may play an important part in solving family conflicts and in children’s emotion regulation through their compassion and wisdom [ 50 ]. In Nepal, few studies on the association between family structure and child EBP have been published.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps institutional knowledge is best understood as a form of “practical wisdom,” which is defined as “making good decisions—doing the right thing, at the right time, for the right reasons” (Jeste et al, 2019, p. 218). Within this framework, it is conceptualized as a set of skills for making wise decisions, displaying comprehensive knowledge about a topic, and demonstrating an intellect guided by moral virtues and social responsibility.…”
Section: How To Survive and Thrive In A New Rolementioning
confidence: 99%